Pengaruh Keterampilan Mengajar Guru Terhadap Hasil Belajar Siswa Melalui Keaktifan Belajar Siswa Sebagai Variabel Moderating Pada Mata Pelajaran Ekonomi Kelas XI IPS di SMA Taman Siswa Pematang Siantar - Juninra Siburian; Herlina Hotmadinar Sianipar; Benjamin Albert Simamora (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research aims to determine the "Effect of Teacher Teaching Skills on Student Learning Outcomes Through Student Learning Activeness as a Moderating Variable in the Economics Subject Class XI IPS at SMA Tamansiswa Pematang Siantar". This type of research is quantitative research with a quantitative descriptive data analysis approach. The research population was students at SMP Negeri 6 Pematang Siantar with a total of 126 students. The sampling technique used was the Slovin sampling technique. Data collection techniques use questionnaires and tests. The hypothesis generation technique uses multiple regression analysis and the coefficient of determination (R2). The research results show that: 1) there is a positive and significant influence of teacher teaching skills on student learning outcomes. This result can be seen in the t test where the calculated t value of teaching skills (5.60) > t table value (1.661) which means the variable is significant. 2) there is a positive influence of student learning activity on student learning outcomes. This result can be seen in the t test where the calculated t value of student learning activity is (4.89) > t table (1.661) which means this variable is significant. 3) the teacher's teaching skills and students' active learning together influence student learning outcomes. This result can be seen in the F test where the Fcount value (8.75) > Ftable value (1.661). The R Square coefficient of determination test found that 27.04% of the variables of teacher teaching skills and student learning activity had an influence on student learning outcomes at Tamansiswa Pematang Siantar High School. Meanwhile, 72.96% is the influence of other variables not examined in this research.Y : 29.90 + 0.43 X1 + 0.44 X2